Experiment Investigation and Numerical Simulation of Snowdrift on a Typical Large-Span Retractable Roof - Cao, Zhenggang; Wu, Pengcheng; Liu, Mengmeng (Complexity (New York, N.Y.), 2019)
Retractable roofs are commonly used in designing large-span stadiums because of their versatility. However, retractable roofs are subject to sudden changes in shape, and thus, factors in addition to those considered for conventional roofs need to be taken into account. In particular, retractable roofs are considerably more sensitive to snow loads because their shapes are complex, and snowdrift on roofs may lead to difficulties for the operating of retractable roofs. To investigate the distribution of snow on retractable roofs, this study proposes a method based on a numerical simulation of snowdrift obtained using the Euler–Euler method in multiphase flow theory. This numerical model employs a mixture model by using the commercial computational fluid dynamics (CFD) software FLUENT. A suitable turbulence model is selected for the simulation through verification against two-dimensional (2D) data obtained from field measurements reported in previous studies. However, the snow load on retractable roofs cannot be determined by a 2D distribution easily. The accuracy of predicting the overall distribution of snow load on roofs was verified by experiments conducted on a horizontally retractable roof. The results show that a nonuniform snow distribution on such roofs is distinct and should be considered.